Pengaruh Sistem Informasi Manajemen SDM Terhadap Pengambilan Keputusan Pengembangan Karir Pada Pt. Bank Tabungan Pensiun Nasional, Tbk, Cabang Manado - Yapary, Fenny Veronika (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstracts: Each employee would want advancement in their careers. This is supported by the company how to implement career development decisions must be exact. There are many factors that influence the decision making process of one's career development, but in this study focused on Information Systems Human Resource Management. How and how much influence Information Systems Human Resource Management for making decisions on career development. This study was conducted at PT. National Pension Savings Bank, Tbk Branch Manado, the hope can be input to the management and employees of the Bank, PT Bank Manado in solving problems for the progress of the company and the existing Human Resource Management. Data collection using field research, and a library research by using the techniques of interview, observation and questionnaire. This study used quantitative methods with simple correlation and regression approach. The answer to the hypothesis can be seen from these results, there is a significant relationship with the value of the correlation (r) 0.76 0.762 the results of determination r2 = 0.5776 which means the variable contribution of human resource management information system in decision-making and career development 57.76% 43.24% influenced by other variables. and test results thit 8.2082. Â Keywords: Information Systems, Human Resource Management, Decision Making Career Development.